First record of late Campanian paieoceanographic and paieociimatic changes, Arabian platform, Mazidag-Mardin area, SE Turkey - Yılmaz, İsmail Ömer; Hosgor, Izzet; Altıner, Sevinç; Wagreich, Michael; Kvacek, Jiri (Carnets de géologie (Notebooks on geology), 2021)
The sedimentology, geochemistry and paleontology of the pelagic upper Campanian Maastrichtian Bozova Formation in the "Mazidag" (Mazidagi) - Mardin area, SE Turkey, reveal paleoceanographic and paleoecological changes for the first time. A 119.25 m -thick composite stratigraphic section is characterized by alternating marls, clayey limestones, shales, and black shales; no coarse siliciclastic admixture or turbidite intercalations were recorded in the section. Biostratigraphic data indicate the presence of the Radotruncana calcarata Zone, and the UC15de/UC16 nannofossil zones. Stable isotope and elemental geochemical analyses have been carried out in the studied section. The isotope curves display similar patterns compared to reference curves from European and Chinese basins in the same interval. The prominent negative carbon isotope excursion determined in the upper interval can be correlated with the Late Campanian Event. Proxy elements display generally two relative rising trends in productivity from the lower part and the middle part of the succession. The lower part of the section records relatively more dysoxic/anoxic conditions and coincides with common black shale beds. The presence of both diverse planktonic foraminifera and calcareous nannofossils in the studied interval indicates a fully marine, warm-water, low-latitude Tethysian oceanic environment. In addition, the plant fossils derived from the nearby land mass indicate that a tropical humid climate was similar to that in northeast Australia. Therefore, warm water, tropical humid atmospheric conditions developed in the studied area causing the rise in productivity, precipitation and transportation of plant debris into offshore environments.